Dyeing and antibacterial properties of cotton dyed with prodigiosins nanomicelles produced by microbial fermentation. (March 2017) - Ren, Yanfei; Gong, Jixian; Fu, Ranran; Li, Zheng; Li, Qiujin; Zhang, Jianfei; Yu, Zhicai; Cheng, Xiaoyu
Abstract: This study focused on dyeing of cotton fabric with nanosuspension of prodigiosins micelles which was produced by the fermentation of Serratia marcescens . The average diameter of the pigments micelles was 184.3 nm (rang of 101.1–378.0 nm). Various factors that affected the dyeing results were analyzed. Furthermore, the antibacterial property of dyed cotton was investigated. It was found that the ethanol concentration, dyeing temperature and dyeing time had great effects on color strength of fabric. When the ethanol concentration of dye bath was 25% (V/V) and the dyeing temperature was set at 90 °C for 90 min, dyed cotton fabric exhibited the maximum K/S value with good rubbing, washing and perspiration color fastness. In addition, due to the presence of prodigiosins, the dyed cotton showed bacteriostatic rate of 51.43% and 94.12% against Escherichia coli and Staphylococcus aureus, respectively. All the results indicated that prodigiosins were successfully dyed onto the cotton fabric via the nanomicelles dyeing method. This research developed a novel method of preparing dye liquid and dyeing cotton with intracellular prodigiosins. Graphical abstract: Highlights: Prodigiosins nanomicelles are produced by the fermentation of Serratia marcescens . Cotton fabric is successfully dyed with the prodigiosins nanomicelles and the optimum dyeing condition is analyzed. Dyed cotton possesses good rubbing, washing and perspiration color fastness. Prodigiosins endow dyed cotton with antibacterial property against S. aureus and E. coli .